Display life and related traits of low-dose irradiated, boneless, pork chops - Luchsinger, S.E.; Garcia Zepeda, C.M.; Chambers, Edgar, IV; Hollingsworth, M.E.; Hunt, Melvin C.; Marsden, James L.; Stroda, Sally L.; Rubio Canas, E.J.; Kastner, Curtis L.; Kuecker, W.G.; Mata, T.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Irradiation and vacuum-packaging caused a more intense and stable red color in boneless pork chops. Irradiation up to 2.5 kGy increased cooked internal redness in chilled chops. Oxidative rancidity was greater in aerobic packaging than vacuum-packaging and in irradiated aerobic packaged chops than controls. Irradiation of vacuum-packaged boneless pork chops has promising potential for market acceptance.
Keywords: Swine; Irradiation; Color; Oxidation